Education and Practice of Complementary Foods Among Mom's Groups on The Kemuning District Banjarbaru Selatan - Ratna Setyaningrum; Nita Pujianti; Mufatihatul Aziza Nisa; Ni Putu Dyan Paramita; I Dewa Ayu Yulia (Jurnal Berkala Kesehatan, 2022)
Stunting is one of the nutrition problems in the world. Nutrition improvement since the womb until the provision of complementary food is needed to solve this problem. Appropriate knowledge and skills in processing complementary foods can be a success factor of good nutritional parenting. This activity aims to provide knowledge and skills about complementary foods among mothers in Kemuning Village. The activity includes preparation, implementation and reporting. The preparation begins with permission and coordination. The implementation involved facilitator namely Lactation Counselors from Association of Indonesian Breastfeeding Mothers (AIMI) in South Kalimantan. Reporting includes activity reports and publications. The activity was held at Posyandu in Kemuning Village attended by 16 participants (mothers who have babies and toddlers) and two representatives from PKB Kemuning and the Head of TP-PKK Kemuning Village. The results through pre and post-test show that the average pretest score of participants is 67.9 and the average posttest score of participants is 77.3. It can be concluded that this activity is effective in increasing the knowledge of participants by 21%. Furthermore, it is necessary to evaluate the improvement of participants' skills.